Effect of CASA, Fee-Based Income, and Intellectual Capital Towards Profitability of Islamic Banking in Indonesia - Fitri, Resfa; Nuraini, Della (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The increase in value of the Current Account Saving Account (CASA) and fee-based income (FBI) in Islamic banking industry is indicative of the optimal use of intellectual capital. This increase in the value of CASA and FBI does not enhance Islamic banking profitability in Indonesia. Therefore, this study aimed to measure and analyze the influence of CASA, FBI, and intellectual capital on profitability of Islamic banks. The populations of this study are all commercial Islamic banks from 2017 to 2020, from which a sample of 13 was selected using the purposive sampling method. Secondary data were collected from quarterly reports of the financial statements of the 13 Islamic banks from 2017 to 2020. This study adopted the panel data regression with a value-added method for the variable intellectual capital (VAIC). The results showed that CASA and intellectual capital had a significant positive effect on Islamic banking profitability, while FBI had no significant effect. It was recommended that in order to enhance banking profitability, the management of Islamic banks needed to improve CASAand intellectual capital by increasing the quantity of CASA funding and optimizing intellectual capital from human resources and technology.